Study guides

☆☆

Q: Is 5x plus 7y plus 3 simplified?

Write your answer...

Submit

Still have questions?

Related questions

1 + 7y = 5x - 2 7y = 5x - 3 - 5x = - 7y - 3 x = 7/5y + 3/5 ---------------------

It can be simplified to: 3+y

8y + 7y = 15ySo [ 8y + 9 + 7y ] = 15y + 9If you want to get fancy and factor that expression, it's 3(5y + 3) .

125x3+343y3 can also be written (5x)3+(7y)3. It helps to rewrite the constants like this because there is a general factoring rule: a3+b3 = (a+b)(a2-ab+b2). In this example, the a is 5x and the b is 7y. Plug in and get (5x+7y)(25x2-35xy+49y2).

7x+2 when simplified by collecting like terms

If you mean: 3y^2-7y+3-5y+3-4y^2 then it is simplified to -y^2-12y+6

If you mean: 2x+3x then it is simplified to 5x

5x plus 3 does equal 3 plus 5x; commutative law.

-6y+3 = -7y+8 -6y+7y = 8-3 y = 5

It is an algebraic expression that can be simplified to: 23x-16

Factors are (5x +1)(x - 3)

5x-8 + 7x 12x-8 12x = 8 x = 8/12 x= 2/3

3 + 5x is the simplest expression of this problem.

An equation or expression with 3 variables. For example... 5x + 7y + 9z is a trinomial.

3/7

It is 5x - 9.

y^2 + 7y + 12 = (y+4)(y+3)

(5x+3)(5x+3) x=(-3/5)

5 over 5x+25yThis is because you combine the two fractions together. 3+2=5 which is the numerator and 5x+25y cannot be simplified which is the denominator.

5x+3 = -17 5x = -17-3 5x = -20 x = -4

-5/7

5x - 3 + 2x + 7 = ?7x + 5 = ?

5x + 3 - 4 + 4x = 9x -1

Let's explain with an example: 2x - 7y = 11 5x + 7y = 3 To solve this system of equations by elimination we "add" the second equation to the first equation. So basically: 2x + 5x - 7y + 7y = 11 + 3 Which then symplifies to: 7x = 14 and x = 2 Then plug x = 2 into the original equation: 5(2) + 7y = 3 Which leads to: y = -1 So the solution is (2,-1).

5x + 3 = -12 5x =-12-3 =-15 x = -3